THE IMPLEMENTATION OF TONGUE TWISTRES FOR TEACHING OF PRONUNCIATION TO THE FOURTH GRADERS (RETAIN, 2013)
Mis-pronounced in English word can create misunderstanding and miscommunication. Word stress has very important in English. A wrong position in word stress in English word can change the meaning. The researcher realized that it is very important to make the students practice pronunciation through such interesting activity as often as possible by using tongue twister. The aims of this study are to describe the implementation of tongue twisters for the teaching of pronunciation for the fourth graders and to describe the students’ responses toward implementation of tongue twisters for the teaching of pronunciation for the fourth graders. The researcher conducted the research in SDN Mojosari 1 and the subject of the study was the fourth graders. The researcher applied a descriptive qualitative research design. From the result of observation checklist and field notes, it could be indicated that the implementation of tongue twisters give some contribution to the students’ pronunciation. From the result of questionnaire, it could be concluded that the students gave good responses toward the use of tongue twister in their class. The researcher suggested that the English teacher should using tongue twisters in teaching English, especially pronunciation by aware of the topics and the level of the students. Keywords: tongue twisters, pronunciation, fourth graders